2014
DOI: 10.1186/1472-6823-14-55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary prebiotic supplementation on advanced glycation, insulin resistance and inflammatory biomarkers in adults with pre-diabetes: a study protocol for a double-blind placebo-controlled randomised crossover clinical trial

Abstract: BackgroundAdvanced glycation endproducts (AGEs) contribute to the development of vascular complications of diabetes and have been recently implicated in the pathogenesis of diabetes. Since AGEs are generated within foodstuffs upon food processing, it is increasingly recognised that the modern diet is replete with AGEs. AGEs are thought to stimulate chronic low-grade inflammation and promote oxidative stress and have been linked to the development of insulin resistance. Simple therapeutic strategies targeted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 111 publications
1
38
0
Order By: Relevance
“…Prebiotics via several mechanisms can improve glycemic status and inflammation. Suppression of the levels of free fatty acids (FFAs) through short-chain fatty acids (acetate, propionate and butyrate) [23] returns to the basal expression levels of transcription factors involved in lipogenesis (sterol regulatory element-binding protein [SREBP-1c]), cholesterol metabolism (SREBP-2, liver X receptors) and fatty acid oxidation (peroxisome proliferator-activated receptor alpha [24] ), reductions of endotoxin levels [25] and decreased oxidative stress [26] , which could improve insulinemic effects. Non-significant changes in FPG may be attributed to lack of RS effect, as a prebiotic, on basal hepatic glucose production [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics via several mechanisms can improve glycemic status and inflammation. Suppression of the levels of free fatty acids (FFAs) through short-chain fatty acids (acetate, propionate and butyrate) [23] returns to the basal expression levels of transcription factors involved in lipogenesis (sterol regulatory element-binding protein [SREBP-1c]), cholesterol metabolism (SREBP-2, liver X receptors) and fatty acid oxidation (peroxisome proliferator-activated receptor alpha [24] ), reductions of endotoxin levels [25] and decreased oxidative stress [26] , which could improve insulinemic effects. Non-significant changes in FPG may be attributed to lack of RS effect, as a prebiotic, on basal hepatic glucose production [27] .…”
Section: Discussionmentioning
confidence: 99%
“…It was originally described as a receptor for protein adducts formed by AGEs that accumulate in diseases such as diabetes and renal failure (Zill, Günther, Erbersdobler, Fölschb, & Faista, 2001). Recently, the inhibitory effect of dietary prebiotic supplementation on advanced glycation was found to be correlated with intestinal microbiota (Kellow et al, 2014). It can be considered that not only low-molecular-weight compounds but also high-molecularweight compounds in the algal AESs, as well as LAB, ameliorate the AGE-related damages with some intestinal microbiota.…”
Section: Anti-glycation Properties Of the Fermented Aqueous Solutionsmentioning
confidence: 98%
“…The anti-glycation properties of the probiotics Lactobacillus acidophilus and Bifidobacterium infantis were recently reported (Stancu, Sanda, Rogoz, & Sima, 2012). Furthermore, one study reported that the prebiotics inulin and oligofructose ameliorated the AGE-related pathology of adult volunteers with pre-diabetes (Kellow, Coughlan, Savige, & Reid, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The research team, headed by the same lead researcher as the abovementioned study, concluded that prebiotics might offer protection against advanced glycation endproducts-related pathology, which contributes to the pathogenesis of diabetes and its vascular complications in persons at risk of developing type 2 diabetes. 45 The researchers noted that the modern Western diet is replete with AGEs in processed foods.…”
Section: Cardiometabolic Disordersmentioning
confidence: 98%